RELAÇÃO ENTRE A SATISFAÇÃO COM SERVIÇOS EDUCACIONAIS E AS CARACTERÍSTICAS PESSOAIS DO RESPONDENTE: ESTUDO COM DISCENTES DE DUAS INSTITUIÇÕES DO ENSINO SUPERIOR DA BAHIA - Santos, Amanayara Carvalho (2012)
Competition for students in higher education has led many researchers to carry out investigations aiming to discover the students' satisfaction with the services provided by institutions that operate in this segment. This work aims to verify the degree of students satisfaction with the educational services delivered by both Social College of Bahia and Maurice of Nassau College, and to analyze the relationship of the results with their personal characteristics. To achieve the goal, the following questions guided the research: (1) what educational factors are formed by means of factor analysis, from the evaluations that the students make of the services provided by these educational institutions? (2) The students' personal characteristics relate to the variables formed by factorial analysis? (3) The students' personal characteristics relate to their satisfaction profiles? The survey was conducted directly by the author of this work in management courses of the two colleges, through a form based on Likert-type survey, with answers filled by the own students. Two hundred and sixty-four respondents gently answered the research questions. The following results were found: (1) seven theoretical factors were formed from the factorial analysis of the students answers; (2) the minority of the relationship between personal characteristics and factors formed by factorial analysis showed statistically significant differences, but the majority showed significant relationship with the degree of satisfaction with the services provided by the colleges. We conclude, therefore, that to say about the influence of personal characteristics of student it is needed to specify the type of analysis.